Assessment of subclinical atherosclerosis with ankle-brachial index in psoriatic arthritis: A case-control study - Serhad BİLİM,; Afitap İÇAĞASIOĞLU,; Ayla AKBAL,; Esen KASAPOĞLU,; Sıdıka GÜRSEL, (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate subclinical atherosclerosis using the Ankle-Brachial Index (ABI) in patients with psoriatic arthritis (PsA). Patients and methods: This case-control study included 51 PsA patients (24 males, 27 females; median age 47; range, 41 to 52 years) recruited at our hospital’s outpatient clinics between October 2016 and January 2017 and 50 healthy controls (24 males, 26 females; median age: 48.5; range, 40.7 to 56 years). Anthropomorphic measurements and laboratory results were recorded. In patients, the 66 swollen/68 tender joints count, dactylitis score, Leeds Enthesitis Index, Health-related Quality of Life, the Psoriasis Area and Severity Index, and Dermatology Life Quality Index were evaluated. Ankylosing Spondylitis Quality of Life and Bath Ankylosing Spondylitis Disease Activity Index were applied to patients with axial disease. Then, Composite Psoriatic Disease Activity Index was determined. A Doppler probe and a standard blood pressure cuff were used to calculate the ABI values for each participant. Results: Patients had lower right ABI (median, 1.05 vs. 1.1, p<0.01), lower left ABI (1.04 vs. 1.09, p<0.01) and lower overall ABI (1.03 vs. 1.09, p<0.01) compared with healthy subjects. Twelve (23.5%) patients had borderline ABI, but none of the controls (p<0.01). Patients with borderline ABI had a longer duration of psoriasis (25 vs. 15 years, p=0.03). The distribution of borderline ABI value was statistically significant between patients with axial disease and peripheral disease only (42.1% vs. 12.5%, p=0.02). Disease activity was found as an independent risk factor for borderline ABI in a binary logistic regression (odds ratio 6.306, 95% confidence interval 1.185 to 33.561, p=0.031). Conclusion: Lower ABI was found in PsA patients than healthy controls even in those matched with traditional cardiovascular risk factors. All participants with borderline ABI were in the patient group. Borderline ABI was associated with disease activity and disease duration.